Propolis in the control of bacterial bovine mastitis: A tool for the production of organic milk - Do Nascimento, Gabriel Michelutti [UNESP]; Cardozo, Marita Vedovelli; Valmorbida, Mylena Karoline [UNESP]; Pereira, Natália [UNESP]; Barbosa, José Carlos [UNESP]; Favaron, Flávio Rubens; De Ávila, Fernando Antônio [UNESP] (Universidade Estadual de Londrina, 2022)
Bovine mastitis is one of the main causes of economic damage in dairy farms. Therefore, the control and prevention of microorganisms involved in this disease, mainly Escherichia coli, Staphylococcus aureus, and Streptococcus agalactiae, are essential. One of the most important steps for the prevention of the disease is the use of antiseptic products before and after the milking process to avoid bacteria from infecting the udder of the animal. Currently, the most used antiseptic product in dairy farms is iodine-based, and organic dairy farms, which follow several strict regulations, including the use of natural products whenever possible, are often forced to adopt non-natural antiseptic products, such as iodine-based ones, because of the lack of natural alternatives. Propolis, a natural substance produced by honeybees, has been extensively studied for its various properties, one of which is antimicrobial activity. Therefore, a new natural antiseptic product containing 1% propolis in 10% hydroalcoholic solution for the pre-dipping, and 10% glycerol solution added with 0.2% citronella oil for the post-dipping was analyzed for its capacity to reduce bacteria in vivo in order to prevent bovine mastitis, allowing its use on organic dairy farms. A total of 128 samples were analyzed in terms of bacterial growth for Enterobacteriaceae and Staphylococcus spp. using the spread-plate technique. The reduction in the bacterial concentration after the application of the products was compared between two antiseptic solutions, an iodine-based solution as the control and a propolis-based one as the natural alternative. The results obtained show a similar efficiency for both products in terms of total bacterial reduction, indicating considerable antimicrobial activity against bacteria most commonly associated with bovine mastitis. Molecular analysis was carried out for the identification of Streptococcus agalactiae; the PCR results were negative for the presence of S. agalactiae in all samples, indicating that the animals most likely did not have any form of the disease. The efficiency of the natural antiseptic was satisfactory, indicating an important find facilitating organic milk production worldwide, showcasing a natural antiseptic solution with efficient antimicrobial activity.
Keywords: Biological control; Egg parasitoid; Enthomopatogenic fungi; Pest insects